PENGARUH PEMAHAMAN PERATURAN PAJAK, PEMERIKSAAN PAJAK, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BADAN - Hidayati, Rezzi; Dewi Astuti, Tutut (ITB AAS Indonesia Surakarta, 2024)
This study aims to determine the factors that influence corporate taxpayer compliance at KP2KP Banjarnegara. Taxes are a very important source of state revenue to finance government spending and the development of public facilities. Taxpayer compliance is one of the crucial aspects in achieving the tax revenue target. In this study, the focus of the variables studied includes understanding tax regulations, tax audits, and tax sanctions, and how these three variables affect the level of compliance of corporate taxpayers. The research method used is a quantitative approach with a sample of corporate taxpayers registered at KP2KP Banjarnegara. The results showed that understanding tax regulations has a significant influence on corporate taxpayer compliance. However, tax audits and tax sanctions do not have a significant effect. The conclusion that can be drawn from this research is that a better understanding of tax regulations can increase the level of compliance of corporate taxpayers. Meanwhile, audit efforts and sanctions need to be evaluated to be more effective in improving tax compliance in the Banjarnegara area. This research is expected to contribute to related parties in an effort to optimize tax revenue. Keywords : Understanding of Tax Regulations, Tax Audit, Tax Sanctions, Tax Compliance